(untitled) (Agricultural Engineering, 2018)
The objective of the paper is to determine the size of human and objectified labour in selected specialist vegetable farms. The paper covered studies carried out in the area of southern Poland in 50 organic vegetable farms. Based on the detailed studies, the size and structure of work, and energy inputs used in the production process were determined. The highest inputs of labour per a unit of the production area and 1 tonne of a product were incurred in production of Cucurbita vegetables – 1883.1 and 547.74 man-hour, while the lowest of Solanacea vegetables – 342.8 and 7.11 man-hour. From among all analysed groups of plants, the highest energy inputs were incurred in cultivation of root and onion vegetables and they were three times higher than in traditional farms. Contrary, the lowest inputs were incurred in cultivation of brassica and Solanaceae vegetables.